Skin tumors with matrical differentiation: lessons from hair keratins, beta‐catenin and PHLDA‐1 expression. (6th March 2014) - Battistella, Maxime; Carlson, John A.; Osio, Amélie; Langbein, Lutz; Cribier, Bernard
<x xml:space="preserve">Abstract</x> Background Pilomatricomas are tumors that emulate the differentiation of matrix cells of the hair follicle, showing cortical differentiation, with sequential expression of K35 and K31 keratins. Beta‐catenin gene is frequently mutated in pilomatricoma, leading to beta‐catenin nuclear accumulation, and to downstream expression of LEF1. Skin matrical tumors other than pilomatricoma are very rare, and comprise purely matrical tumors and focally matrical tumors. We aimed at studying cortical differentiation, beta‐catenin pathway and expression of the follicular stem‐cell marker PHLDA1 in a series of matrical tumors other than pilomatricoma. Methods In 36 prospectively collected tumors, K31, K35, CK17, LEF1, HOXC13, beta‐catenin and PHLDA1 expressions were evaluated. Five pilomatricomas were used as controls. Results In 18 purely matrical tumors (11 matrical carcinomas, 4 melanocytic matricomas, 3 matricomas) and 18 focally matrical tumors (11 basal cell carcinomas, 3 trichoepithelioma/trichoblastomas, 4 others), sequential K35, HOXC13 and K31 expressions were found, indicating cortical differentiation. Germinative matrix cells were always CK17–, and showed nuclear beta‐catenin accumulation, with LEF1 and PHLDA1 expressions. Conclusions Nuclear beta‐catenin and LEF1 expression was highly conserved in matrical tumors, and suggested a common tumorigenesis driven by Wnt pathway activation. PHLDA1 was consistently expressed in matrical tumors and in areas of matrical differentiation.